Recent evolution of the active layer in the morenas coloradas rock glacier, central andes, mendoza, argentina and its relation with kinematics - Trombotto, Dario Tomas; Bottegal, Estefania Laura (Cuadernos de Investigación Geográfica)
Between 2008 and 2016 the Morenas Coloradas rock glacier in the Central Andes of Mendoza showed different thermal characteristics at three monitoring sites in active layers, Balcón I (3560 m a.s.l.), Balcón I Superior (3590 m a.s.l.) and Balcón II (3770 m a.s.l.). These can be explained by various factors, not only external ones related to the climatic variability and altitude, but also by thermal-hydrological factors that destabilized its internal cryogenic structure. At Balcón I, situated on a sloping terrace of the rock glacier, a transient layer even showed definitive signs of permafrost degradation in the recent years, transforming it in a thermal talik. Long-term studies of surficial boreholes showed that the 0°C isotherm is higher in altitude than the active front of the rock glacier and it has risen 40 m in altitude since the 1990s. As consequence of the thermal changes of the active layer, the rock glacier shows abrupt movements, particularly in its terminal part. Thus geodesic measurements to obtain different speeds and directions were made. At the monitoring area of Balcón I Superior, which lies on a superimposed lobe, the geodesic measurement points revealed significant kinematic activity in the period May 2015 – February 2016, when the largest displacement was approximately 2 m to the South, developing an advance of the front over Balcón I. At Balcón II however, the points moved much less, in the order of 0.30 m yr-1. The present studies suggest that the largest cryogenic sedimentary movements are superficial, that is to say, they are located in the active layer and the supra-permafrost and are due to internal movements produced by melting water coming from the top of the cryoform, and from both sides of the upper basin of the valley. En el período 2008-2016 el glaciar de escombros de Morenas Coloradas, en los Andes Centrales de Mendoza, presentó en sus sitios de monitoreo Balcón I (3560 m s.n.m.), Balcón I Superior (3590 m s.n.m.) and Balcón II (3770 m s.n.m.) situaciones térmicas de capa activa ...